Harnessing CRISPR-Cas for Stress Tolerance and Yield Improvement in Cotton - Aswathy Rajan (15991511) (2025)
Cotton plays a crucial role in the global economy, serving as a primary source of natural fiber, high-quality protein, and oil. However, increasing demand driven by population growth, coupled with the escalating impact of abiotic and biotic stresses, poses significant challenges for sustainable cotton production. Enhancing stress tolerance and yield is, therefore, critical to ensure stable production and meet global demands. Conventional breeding strategies, though effective, are time-consuming and often constrained by genetic bottlenecks and complex trait inheritance. In contrast, CRISPR-Cas systems have emerged as powerful tool for accelerating genetic improvement in cotton due to its unique combination of simplicity, high efficiency, and broad applicability that distinguish it from earlier genome editing technologies. This system enables precise modulation of gene expression, enhancement of resistance to both biotic and abiotic stresses, and the ability to stack multiple genes to control essential agronomic traits. Furthermore, the development of transgene-free genome editing approaches through CRISPR enhances its regulatory acceptance by avoiding the incorporation of foreign DNA, thereby addressing public and biosafety concerns associated with genetically modified organisms, making it a valuable platform for next-generation cotton breeding. This review highlights the current progress and future prospects of CRISPR-Cas technology in addressing key challenges associated with cotton productivity, fiber quality, and adaptation for developing high-yielding and stress-resilient cultivars.